Preclinical Evaluation of HPV Type 52 L1L2 Chimeric Protein as a Cervical Cancer Vaccine Candidate - Sari, Isti Kartika; Pamungkas, Joko; Mustopa, Apon Zaenal; Wibawan, I Wayan Teguh; Mamangkey, Jendri; Chairunnisa, Sheila; Irawan, Herman; Hertati, Ai; Ekawati, Nurlaili; Umami, Rifqiyah Nur; Novianti, Ela; Nurfatwa, Maritsa; Darusman, Huda Shalahudin (HAYATI Journal of Biosciences, 2026)
High-risk human papillomaviruses (HPVs) are the primary etiological agents of cervical cancer, accounting for more than 300,000 deaths annually worldwide. Current prophylactic vaccines based on recombinant L1 major capsid virus-like particles (VLPs) have demonstrated strong efficacy but are restricted to a limited spectrum of HPV types. To address this limitation, the present study evaluated a recombinant L1L2 chimeric protein derived from HPV type 52 as a potential candidate for a broad-spectrum vaccine. The chimeric protein was expressed in Escherichia coli strain BL21 (DE3) and purified for immunization studies. Female BALB/c mice (Mus musculus, n = 5 groups) were immunized, and immune responses were analyzed by enzyme-linked immunosorbent assay (ELISA) and pseudovirion-based neutralization assays (PBNA). The recombinant L1L2 vaccine candidate induced detectable antibody responses against HPV antigens; however, neutralizing activity remained modest. Histopathological analysis of liver and kidney tissues showed no evidence of toxicity, supporting the safety profile of the candidate. In summary, these results suggest that the HPV type 52 L1L2 chimeric protein represents a promising platform for the development of cervical cancer vaccines, although further optimization is required to achieve robust cross-neutralizing efficacy.